2015
DOI: 10.4082/kjfm.2015.36.4.180
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coronary Patients with Severe Chest Pain Show More Irrational Beliefs Compared to Patients with Mild Pain

Abstract: BackgroundDespite providing insufficient medical evidence of the existence of a real cardiac condition, patients with non-coronary chest pain still interpret their pain incorrectly. The present study, therefore, sought to compare the irrational beliefs in non-coronary patients with mild chest pain against those with severe chest pain.MethodsA cross-sectional design was used. The statistical population comprised non-coronary patients who presented to the Heart Emergency Center of Kermanshah city, Iran. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…In line with the results of several studies regarding the relationship between psychological symptoms and pain severity and discomfort in patients with noncardiac chest pain,[4567] our results showed that psychological symptoms are an important factor in the pain severity and discomfort experienced by cardiac patients. According to the results, anxiety is the most important factor in the pain severity and discomfort experienced by patients.…”
supporting
confidence: 91%
“…In line with the results of several studies regarding the relationship between psychological symptoms and pain severity and discomfort in patients with noncardiac chest pain,[4567] our results showed that psychological symptoms are an important factor in the pain severity and discomfort experienced by cardiac patients. According to the results, anxiety is the most important factor in the pain severity and discomfort experienced by patients.…”
supporting
confidence: 91%
“…Individuals' perception of CVDs-related risk factors is of the components that can affect health behaviors. Clearly, more than anything else, behaviors are affected by the thoughts, beliefs, and attitudes of individuals (13). The attitudes of patients with CVDs regarding the diseases risk factors play a central role in mental and physical health and healthy behaviors (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…For example, psychodynamic theory suggests conflicts, while cognitive theory focuses on dysfunctional thoughts and irrational beliefs. According to cognitive theory, the irrational beliefs often have an automatic, unconscious, and permanent nature (6), and they play an important role in the development and continuation of substance abuse (7). The cognitions and beliefs of patients have a significant impact on the course and progression of all phases of this disorder experience, including understanding the signs, looking for causes, and changes in individual behavior (8).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the findings of previous studies (27,44). Due to the family, social, and economic conditions of most addicts, high levels of anxiety can be predicted 6 Int J High Risk Behav Addict. 2017; 6(1):e31450.…”
mentioning
confidence: 99%